2016
DOI: 10.1186/s40794-016-0024-y
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and practices regarding dengue infection among public sector healthcare providers in Machala, Ecuador

Abstract: BackgroundDengue fever is a rapidly emerging infection throughout the tropics and subtropics with extensive public health burden. Adequate training of healthcare providers is crucial to reducing infection incidence through patient education and collaboration with public health authorities. We examined how public sector healthcare providers in a dengue-endemic region of Ecuador view and manage dengue infections, with a focus on the 2009 World Health Organization (WHO) Dengue Guidelines.MethodsA 37-item question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 16 publications
6
41
1
4
Order By: Relevance
“…In prior studies in Machala, community members and healthcare professionals indicated that there was low health care seeking behavior in certain populations, such as working men in the urban periphery, and self-medicating was common practice. 18,71 Another explanation is that our definition of symptomatic DENV infections included mildly symptomatic infections that did not require medical attention. These findings highlight the importance of active surveillance protocols that capture inapparent infections and infections in demographic groups who are less likely to seek health care or who have limited access to health care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In prior studies in Machala, community members and healthcare professionals indicated that there was low health care seeking behavior in certain populations, such as working men in the urban periphery, and self-medicating was common practice. 18,71 Another explanation is that our definition of symptomatic DENV infections included mildly symptomatic infections that did not require medical attention. These findings highlight the importance of active surveillance protocols that capture inapparent infections and infections in demographic groups who are less likely to seek health care or who have limited access to health care.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially important in places and in subgroups with low healthcare seeking behavior, which result in underreporting and continued disease transmission. 18,71 Enhanced surveillance systems have been shown to detect an increase in infections earlier than passive surveillance systems, 25 providing a warning of an escalating outbreak. These data are currently being used to parameterize and calibrate local epidemic forecast models.…”
Section: Discussionmentioning
confidence: 99%
“…Demographic differences between symptomatic and asymptomatic cases may have introduced bias in earlier studies. In Machala, community members reported that working men in the urban periphery are the group least likely to seek healthcare [25], and health care providers [63] supported this notion; therefore, prior studies based on MOH case reports would have underestimated their risk of infection. Also, this study focused on data from individual households rather than neighborhood-level data, and may have therefore been better suited to tease out factors related to the spread of DENV between households.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study on the perception of the present and future risk of vector-borne diseases (i.e., dengue, [33][34][35][36], H1N1pdm flu [37][38][39] and H5N1 avian flu [40][41][42]; others have focused on general practitioners in France [43][44][45], both general population and practitioners [46], French pharmacists [47] or risk perception in Europe and other countries worldwide [48][49][50]. The appearance of various emerging infectious diseases during the last two decades (e.g., chikungunya, SARS-CoV, MERS-CoV, Ebola virus, Zika), as well as that of antibiotic-resistant bacteria, has stimulated research on risk perception in the general public and policy-makers [51][52][53][54][55].…”
Section: No Studies On the Arboviral Disease Risk Perception By Healtmentioning
confidence: 99%